Huangqi Guizhi Wuwu Decoction Improves Arthritis and Pathological Damage of Heart and Lung in TNF-Tg Mice - Wang, Yi; Chen, Tao; Yang, Can; Li, Qiang; Ma, Mengjiao; Xu, Hao; Shi, Qi; Wang, Yongjun; Wang, Youhua; Liang, Qianqian (Frontiers in Pharmacology, 2022)
In order to study whether Huangqi Guizhi Wuwu Decoction (HGWD) can alleviate the pathological changes caused by rheumatoid arthritis and cardiopulmonary complications, five 3-month-old TNF-Tg mice were treated with HGWD (9.1g/kg) once a day or the same dose of normal saline lasted for 8 weeks, and WT littermates of the same age were used as a negative control, and methotrexate (MTX) was intraperitoneally administered as a positive control. After the treatment, pathological staining was performed on the mouse ankle joints, heart and lungs, and it was found that HGWD reduced the inflammation of the ankle joint synovium in TNF-Tg mice, as well as reduced myocardial hypertrophy, heart pneumonia infiltration and fibrosis. Immunohistochemical staining with anti-TNF-α antibody showed that HGWD reduced the expression of TNF-α in the heart of TNF-Tg mice. In conclusion, HGWD alleviates joint inflammation in TNF-Tg mice and reduces the pathological changes of the heart and lungs.